Study on the Influence of Small Attitude Angle on Lidar Wind Measurement Results. (July 2018) - Dou, Peilin; Zhang, Xin; Han, Xiaochen; Xue, Yangyang
Abstract: When carrying on wind profile measurement of offshore wind farm by Floating Doppler lidar technique, the platform often produces motion response under the action of ocean environment load. The motion response affects the accuracy of lidar wind measurement.In this paper, the synchronous observer experiment is designed to study the influence of small attitude angle on the accuracy of laser radar's wind measurement, giving an example of comparing the wind measurement data of two lidars, and carrying out the linear regression statistical analysis for all the experimental correlation data.It is found through experiments that the small attitude angle has less influence on horizontal wind speed and wind direction, and has a greater impact on vertical wind speed.